Kinematic analysis of compensation movements of upper limb amputees and able-bodied individuals during grasping movements - Gabriela Machlowiec 1998- (2023)
Upper limb prostheses users make compensatory movements to be able complete daily tasks. The primary compensation occurs from the next distal joint nearby the amputation. For transradial prosthesis users, the main compensatory movements often occur because of limited degrees of freedom and lack of control in the prosthetic wrist. Compensatory movements have been associated with musculoskeletal complaints (MSC), overuse injuries, and repetitive strain injuries (RSI), which are serious issues that may have long-term and chronic effects on a patient. This study aimed to investigate the kinematic analysis of compensation movements of transradial amputees compared to able-bodied individuals during grasping movements and performing Clothespin Relocation Test (CPRT). The study included kinematic analysis of the shoulder abduction-adduction, elbow flexion-extension and upper and lower trunk lateral bending. Nine able-bodied individuals and two transradial prostheses users participated in the study. Both prosthesis users had over two years of experience with the device and use it daily. The device that the amputees used was i-Limb Quantum, Össur. The CPRT was divided into two different assessments, where the participants performed an upward and downward assessment. Moreover, six various analyses were performed for both assessments; the comparison of the right and hands hand of able-bodied subjects and both prostheses users, a comparison of not affected and affected side of prostheses users, and a comparison of able-bodied subjects and prostheses users. The project cooperated with Össur hf (Reykjavik, Iceland and Livingston, United Kingdom).